(untitled) (International Journal of Engineering and Computer Science, 2018)
Most of major IT projects failed due to its complexity and the project complexity is determined by the intensity of business requirements and its fluctuant nature. Prince2 is the solution for a sophisticated project because of its vast range of stage driven processes which mainly focus on project benefits in each stage. The main objective of Prince2 is breaking the complexity into small parts/stages which can be achieved easily. The seven processes of Prince2 cover the entire project lifecycle including requirement gathering, as-is process, development, and product delivery. The seven themes cover major concerns of any project including business case, risk management and quality on deliverables. The seven principles are the seven pillars of Prince2 which sustain its standard. It is understood that the Agile project management methodology is suitable for medium and small scaled projects. The five groups processes of Agile project management intensely focus on development activities and make sure the required product is delivered without any error. It is recommended that Prince2 is certainly suitable for complex projects as a dominant project management methodology, however, Scrum technique can be used for depth IT development as a secondary project management methodology within Prince2.